Dimers for type D relativistic Toda model - Kimyeong Lee; Norton Lee (Journal of High Energy Physics)
Abstract We construct dimer graphs for type D relativistic Toda models by introducing impurities into the Y 2N,0 square dimer graphs. By properly placing the impurities and changing the canonical variables assigned to the 1-loops on the dimer graph, we perform a “folding” of the graphs, which yields the type D relativistic Toda lattice Hamiltonian and monodromy matrix.